Potential of culture filtrate from Trichoderma spp. as biofungicide to Colletotrichum gloeosporioides causing anthracnose disease in chili - Nurbailis Nurbailis; AKMAL DJAMAAN; HALIATUR RAHMA; YENNY LISWARNI (Society for Indonesian Biodiversity, 2019)
Abstract. Nurbailis, Djamaan A, Rahma H, Liswarni Y. 2019. Potential of culture filtrate from Trichoderma spp. as biofungicide to Colletotrichum gloeosporioides causing anthracnose disease in chili. Biodiversitas 20: 2915-2920. Trichoderma spp. have the potential to be used for controlling the airborne pathogenic fungi such as C. gloeosporioides. The purpose of this study was to evaluate the antifungal activity of the culture filtrate of five isolates of Trichoderma spp. (T. harzianum, T. viride, T. koningii, Trichoderma PP2, Trichoderma PP3) against C. gloeosporoides causing anthracnose disease in chili. Culture filtrate of Trichoderma spp. was produced from single culture and dual culture techniques. The design was a Completely Randomized Design with six treatments and four replications. The treatments were culture filtrate from T. harzianum, T. viride, T. koningii, Trichoderma PP2, Trichoderma PP3, and negative control (without culture filtrate from Trichoderma spp.). Parameters observed were: the diameter of the colony, colony coverage, conidial germination, and conidial density. The results of this research showed all the culture filtrate from Trichoderma spp. produced by single and dual culture techniques can inhibit the growth of C. gloeosporioides. The culture filtrate from Trichoderma PP2 and T. koningii were the most potential in inhibiting the growth, conidial density, and conidial germination of C. gloeosporioides.